Estudo da ação antimicrobiana e imunomoduladora de produtos naturais associados - MENDES, Priscila Mendonça (2023)
Cutaneous wound healing is a highly complex and dynamic mechanism aimed at restoring damaged tissue. However, several factors can interfere with the normal repair of wound healing, such as infections, which cause continuous and persistent inflammation, resulting in excessive healing and the formation of fibroproliferative scars, including keloids and hypertrophic scars. These conditions can lead to functional and aesthetic losses, making proper development of this process crucial for maintaining skin function. The aim of this study was to review the literature on the therapeutic potential of the Punica granatum species and to investigate the immunomodulatory and antibacterial potential of a nanoemulsion containing the association of natural products (PPG) on a murine model of wounds infected with methicillin-resistant Staphyloccocus aureus (MRSA). Chapter I is entitled: "Therapeutic Potential of Punica granatum and its Isolated Compounds: Evidence-Based Advances for Treating Bacterial Infections" and Chapter II presents the experimental study of the treatment of infected wounds using the formulation containing a combination of natural products. In the experimental study, excisional wounds (78.5 mm2 ) were induced on the back of female Swiss mice, the animals were allocated to three groups (n=14), including negative control (CTRL); Fibrinase® (DFC, positive control); a nanoemulsion containing the association of natural products (PPG). After lesion induction, the infected groups received approximately 1.5×108 CFU/wound and were treated daily from day 1 to day 10 post-infection. The diameter of the wound and the percentage of healing were investigated using ImageJ software. Macroscopic analysis of the wounds was carried out every other day. At random, animals from each group were euthanized on days 3, 7 and 10 and then the skin from the injured area was removed for analysis of histological parameters (epithelialization, inflammatory cell infiltration (PMN), fibroblast proliferation, collagen deposition and angiogenesis). The levels of inflammatory mediators (IL-2; IL4; IL-6; IFN-γ; TNF- α; IL-17A; IL-10) were measured in the serum and the count of colony-forming units (CFU) present in the wounds was analyzed to verify the antibacterial activity of PPG at the three time points. Topical treatment of wounds in mice with infected lesions induced complete wound retraction on day 10 in all groups. Topical application of PPG was able to significantly (p < 0.05) increase macrophage proliferation (p=0.013; CTRL= 2.33±0.51; DFC=.33±0.51; PPG=2.33±0.51) and reduce the PMN index (p=0.038; CTRL=2.33±0.51, DFC=1.66±0.51; PPG=2.00±0.81) on the 7th day of treatment. In addition, it was able to increase collagen deposition on day 10 (p=0.038; CTRL=2.33±0.51; DFC=2.33±0.51; PPG=3.00±0.00) and angiogenesis (p=0.023; CTRL=1.50±0.57; DFC=2.00±0.00; PPG=2.33±0.51). The positive effects of PPG treatment on reducing bacterial load on days 7 (CTRL=9.71±0.14; DFC=9.72±0.04; PPG=9.39±0.22 Log CFU/mL) and 10 (CTRL=10.67±0.09; DFC=10.18±0.11; PPG=10.31±0.22 Log UFC/mL) and increased IFN-γ (p= 0.0373; CTRL=0.00±0.00; DFC=0.04±0.11; PPG=0.76±1.32). In conclusion, the nanoemulsion proved to be a promising alternative for the treatment of infected wounds, not only for its effect in controlling the infectious agent, but also for promoting effective tissue repair. These events are directly related to the improvement in the appearance of the injured area, highlighting the potential clinical application of PPG gel as a therapeutic approach for infected wounds, with a positive impact on the quality and effectiveness of the healing process.